Antiproliferative and Microtubule-stabilizing Activities of Two Iboga-vobasine Bisindoles Alkaloids from Tabernaemontana corymbosa in Colorectal Adenocarcinoma HT-29 Cells - Tan, Chun Hoe; Sim, Dawn Su Yin; Lim, Siew Huah; Mohd Mohidin, Taznim Begam; Mohan, Gokula; Low, Yun Yee; Kam, Toh Seok; Sim, Kae Shin (Planta Medica, 2022)
Two iboga-vobasine bisindoles, 16′-decarbomethoxyvoacamine (1) and its 19,20-dihydro derivative, 16′-decarbomethoxydihydrovoacamine (2) from Tabernaemontana corymbosa exhibited potent cytotoxicity against the human colorectal adenocarcinoma HT-29 cells in our previous studies. Bisindoles 1 and 2 selectively inhibited the growth of HT-29 cells without significant cytotoxicity to normal human colon fibroblasts CCD-18Co. Treatment with bisindoles 1 and 2 suppressed the formation of HT-29 colonies via G0/G1 cell cycle arrest and induction of mitochondrial apoptosis. Owing to its higher antiproliferative activity, bisindole 2 was chosen for the subsequent studies. Bisindole 2 inhibited the formation of HT-29 spheroids (tumor-like cell aggregates) in 3D experiments in a dose-dependent manner, while an in vitro tubulin polymerization assay and molecular docking analysis showed that bisindole 2 is a microtubule-stabilizing agent which is predicted to bind at the β-tubulin subunit at the taxol-binding site. The binding resulted in the generation of ROS, which consequently activated the oxidative stress-related cell cycle arrest and apoptotic pathways, viz., JNK/p38, p21Cip1/Chk1, and p21Cip1/Rb/E2F, as shown by microarray profiling.
Keywords: Tabernaemontana corymbosa; Apocynaceae; 16′-Decarbomethoxyvoacamine; 16′-Decarbomethoxydihydrovoacamine; Apoptosis; G0/G1 phase arrest